Quantifying the impact of tillage measures on the cultivated-layer soil quality in the red soil hilly region: Establishing the thresholds of the minimum data set. (November 2021) - Jin, Huifang; Zhong, Yijun; Shi, Dongmei; Li, Junkai; Lou, Yibao; Li, Yanli; Li, Jifu
Highlights: Established the Minimum data set (MDS) indicators for cultivated-layer soil quality (CLSQ) diagnosis. The CLSQI was generally between the reasonable (III) and unreasonable (IV) levels of red soil sloping farmland in southern China . Defined the thresholds of MDS indicators for reasonable cultivated-layer construction. Subsoiling is recommended for the recovery and improvement of CLSQ, and compaction exert an adverse impact on it. Abstract: Tillage is known to potentially affect soil quality in various ways, and employing appropriate tillage measures is crucial to construct a reasonable cultivated layer (RCL), which could maximize the storage and coordination of water, gas and heat conditions in the cultivated layer of red soil sloping farmland. This study aims to 1) select the key indicators to establish a minimum data set (MDS), 2) evaluate the quality of cultivated-layer soil and define the indicator threshold for RCL construction, and 3) develop a credible cultivated-layer soil quality index (CLSQI) for the cultivated layer with different tillage measures, and screen suitable tillage measures to improving the soil productivity of red soil sloping farmland. Taking the red soil sloping farmland in China as the research focus, the MDS is established by principal component analysis (PCA) in conjunction with the norm value, Furthermore, the membership function models (S type, anti-s-type, Parabola-type) are used to normalize the indicator data and then assess the CLSQ based on the CLSQI approache, determine the indicator threshold by the CLSQ grade and membership function model, and analyse the cultivated-layer improvement effect by different tillage measures. The results indicated that the MDS and the thresholds of six indicators defined as the cultivated-layer thickness (CLT ≥ 20.39 cm), saturated hydraulic conductivity (SHC ≥ 6.24 mm/min), shear strength (SS ≥ 3.16 kg/cm 2 ), clay content of 10.0–28.1%, organic matter (OM ≥ 15.23 g/kg) and available phosphorus (AP ≥ 58.48 mg/kg), were established in this research for the soil quality assessment of red soil sloping farmland. Tillage methods notably influenced these indicators and CLSQ, and the CLSQI was the highest for subsoiling (0.58) and lowest for soil compaction (0.37); however, mechanical compaction imposed a negative impact on the CLSQ under agricultural modernization, so subsoiling was the recommended measure for the production of soil conditions in this area. Our findings demonstrated that the sloping farmland resources in the research area should be reasonably utilized for the construction of an RCL, and effective subsoiling was suggested for good recovery of cultivated-layer soil capacity and function to increase the CLSQ. Smallholder farmers should therefore be aware of the potential for high soil quality in the future as a result of subsoiling and maintain the soil indicators at a suitable or even high level.